Controlling alloy formation and optical properties by galvanic replacement of sub-20 nm silver nanoparticles in organic media1. Issue 36 (28th September 2015) - Collins, G.; McCarty, E. K.; Holmes, J. D.
<x xml:space="preserve">Abstract</x> Galvanic replacement is a versatile synthetic strategy for the synthesis of alloy and hollow nanostructures.